Community-acquired Respiratory Viruses Are a Risk Factor for Chronic Lung Allograft Dysfunction. (17th December 2018) - Peghin, Maddalena; Los-Arcos, Ibai; Hirsch, Hans H; Codina, Gemma; Monforte, Víctor; Bravo, Carles; Berastegui, Cristina; Jauregui, Alberto; Romero, Laura; Cabral, Evelyn; Ferrer, Ricard; Sacanell, Judith; et al.
Abstract: Background: The relationship between community-acquired respiratory viruses (CARVs) and chronic lung allograft dysfunction (CLAD) in lung transplant recipients is still controversial. Methods: We performed a prospective cohort study (2009–2014) in all consecutive adult patients (≥18 years) undergoing lung transplantation in the Hospital Universitari Vall d'Hebron (Barcelona, Spain). We systematically collected nasopharyngeal swabs from asymptomatic patients during seasonal changes, from patients with upper respiratory tract infectious disease, lower respiratory tract infectious disease (LRTID), or acute rejection. Nasopharyngeal swabs were analyzed by multiplex polymerase chain reaction. Primary outcome was to evaluate the potential association of CARVs and development of CLAD. Time-dependent Cox regression models were performed to identify the independent risk factors for CLAD. Results: Overall, 98 patients (67 bilateral lung transplant recipients; 63.3% male; mean age, 49.9 years) were included. Mean postoperative follow-up was 3.4 years (interquartile range [IQR], 2.5–4.0 years). Thirty-eight lung transplant recipients (38.8%) developed CLAD, in a median time of 20.4 months (IQR, 12–30.4 months). In time-controlled multivariate analysis, CARV-LRTID (hazard ratio [HR], 3.00 [95% confidence interval CI, 1.52–5.91]; P = .002), acute rejection (HR, 2.97 [95% CI, 1.51–5.83]; P = .002), and cytomegalovirus pneumonitis (HR, 3.76 [95% CI, 1.23–11.49]; P = .02) were independent risk factors associated with developing CLAD. Conclusions: Lung transplant recipients with CARVs in the lower respiratory tract are at increased risk to develop CLAD. Abstract : "Community-acquired respiratory viruses (CARVs) lower respiratory tract infection" should be better than viral lower respiratory tract infection. It should be: CARVs lower respiratory tract infection, acute rejection and cytomegalovirus pneumonitis were independently associated with chronic lung allograft dysfunction.